2022
DOI: 10.1155/2022/7021384
|View full text |Cite|
|
Sign up to set email alerts
|

Investigating the Impact of Bank Housing Credit Risk Control Strategy by Blockchain Technology on the Household Consumption Plan

Abstract: It is essential to solve the problem of information asymmetry in bank housing credit management, thus reducing bank operating costs and credit risk. Therefore, the present work constructs a bank housing credit blockchain alliance system based on the technical characteristics of blockchain to strengthen bank housing credit risk control. First, according to blockchain’s elements and system architecture, the application of blockchain to bank housing credit business is analyzed. On this basis, the bank housing cre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Currently, researchers have applied the blockchain technology in data storage, such as student credit management [53], achievement management [54], and career data management in nonformal education [55]. Liang et al implemented PDPChain [56] for secure storage of personal education data, and the blockchain network in the framework guaranteed the trusted storage of the private data by using a consortium chain.…”
Section: Educational Data Storagementioning
confidence: 99%
“…Currently, researchers have applied the blockchain technology in data storage, such as student credit management [53], achievement management [54], and career data management in nonformal education [55]. Liang et al implemented PDPChain [56] for secure storage of personal education data, and the blockchain network in the framework guaranteed the trusted storage of the private data by using a consortium chain.…”
Section: Educational Data Storagementioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%